Green Economy sebagai Paradigma Baru Pembangunan Ekonomi Nasional - Hermanto Hermanto; Ahyar Rosidi (Lembaga Publikasi Ilmiah Nusantara, 2026)
The concept of the green economy has developed as a response to the various problems arising from conventional economic development, which has primarily focused on economic growth without adequately considering environmental carrying capacity and the sustainability of natural resources. Traditional development models have been proven to generate negative impacts such as environmental degradation, climate change, excessive resource exploitation, and widening social inequality. Therefore, the green economy emerges as an alternative approach that emphasizes the integration of economic growth, social equity, and environmental preservation within a sustainable development framework. This study aims to analyze how the green economy can serve as a new paradigm in national economic development and to identify the opportunities and challenges of its implementation across various strategic sectors. The research method employed is a descriptive qualitative approach through literature review and analysis of national and international policy documents related to sustainable development, renewable energy, green industry, and natural resource management. The findings indicate that the application of green economy principles has the potential to enhance energy and resource efficiency, promote environmentally friendly technological innovation, expand green jobs, and strengthen national economic competitiveness in the global market. Moreover, the green economy can serve as an instrument for poverty reduction through the development of environmentally based local economies and community empowerment. However, the implementation of the green economy still faces several challenges, including limited comprehensive regulations, low levels of environmental literacy among the public, high initial investment requirements, and resistance from conventional industrial sectors. Therefore, synergy among the government, private sector, academia, and society is required in the form of integrated policies, economic incentives, public education, and strengthened technological innovation to ensure that the transition toward a green economy proceeds effectively and sustainably. In this way, the green economy becomes not merely a discourse, but a concrete strategy for inclusive, equitable, and long-term oriented national economic development.